Investigating the Role of Management Accountants in Indonesia - Fadhilah, Arief; Harahap, Siti Nurwahyuningsih; Setyaningrum, Dyah (Universitas Prasetiya Mulya, 2015)
Literature highlight the role of management accountants as business partners in managerial decision making process besides the traditional role as information providers. This study investigates the role of management accountants in Indonesia by adopting the DeLone and McLean Information System Success Model (2003). Data were collected by conducting surveys to acquire the perception of managers on the role of management accountants. Using structural equation modeling, the results show that both management accounting information quality and management accounting service quality have significant relationship with user satisfaction. Furthermore, the satisfaction of managers is positively related to net benefits received by managers. Therefore, management accountants in Indonesia may have fulfilled the role as business partners.